KHASIAT ALOE VERA DAN MADU TOPIKAL PADA RE-EPITELISASI DAN PEMBENTUKAN JARINGAN GRANULASI LUKA EKSISI KULIT TELINGA KELINCI - Kalangi, Sonny J. R. (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: There are still conflicting opinions about the benefits of aloe vera and honey in accelerating wound re-epithelialization. This study aimed to compare the efficacy of the topical application of honey, aloe vera, and normal saline solution on re-epithelialization and granulation tissue formation on skin wound healing. Six white rabbits were used for evaluation. Four full-thickness excisional wounds were made on the interior surface of each ear with a 6-mm tissue punch. The forty-eight wounds were treated either with aloe vera, honey, or normal saline, or left untreated (as control group). On day 7 after treatment, the wound tissues were processed for histological examination. Histological cross sections, stained with hematoxylin-eosin, were used for a quantitative evaluation of re-epithelialization and granulation tissue formation. Re-epithelialization was evaluated by measuring the distance of epithelial gaps. Granulation tissue formation was followed-up by measuring the height of the granulation tissue, the distance of granulation tissue gaps, the total lateral-medial distance of granulation tissue, and by calculating the value of granulation tissue volume. The values of the acceleration rate of the re-epithelialization were found to be statistically significant (P < 0.05): topical aloe vera (P = 0.003) and honey (P = 0.004). Except for the height of the granulation tissue (P = 0.054), all other values of the tissues showed results which were significantly different. The acceleration of the formation of the granulation tissue found in the tissue treated with aloe vera and honey generated in the medio-lateral direction toward to the center of the wound. Conclusion: The re-epithelialization processes and the formation of the granulation tissue in the full-thickness wounds performed on the rabbit ears were significantly increased by the topical treatment of aloe vera or honey. The treatment with aloe vera on those healing processes had the same effectiveness as that of honey. Keywords: aloe vera, honey, re-epithelialization, granulation tissue formation Â Â Abstrak: Aloe vera dan madu dianggap dapat mempercepat re-epitelisasi luka sekalipun masih terdapat beberapa perbedaan pendapat. Penelitian ini bertujuan membandingkan khasiat aloe vera, madu, dan larutan garam fisiologis yang diberikan secara topikal dalam re-epitelisasi dan pembentukan jaringan granulasi pada proses penyembuhan luka eksisi kulit telinga kelinci. Sebanyak 6 ekor kelinci putih jantan dipakai sebagai sampel. Pada telinga kelinci dibuat luka eksisi sedalam tebal kulit berbentuk bundar dengan diameter 6 mm. Setiap telinga dibuat empat buah luka pada permukaan dalam telinga. Luka kemudian mendapat perlakuan pemberian aplikasi topikal larutan NaCl 0,9%, madu, dan aloe vera, serta kontrol yang tidak diobati. Tujuh hari kemudian dilakukan biopsi pada sediaan luka. Jaringan diproses menjadi sediaan histologik dan dipulas dengan hematoksilin eosin untuk penilaian secara kuantitatif terhadap proses re-epitelisasi dan pembentukan jaringan granulasi. Re-epitelisasi dinilai dengan cara mengukur jarak celah epitel. Pembentukan jaringan granulasi dinilai dengan cara mengukur tinggi jaringan granulasi, jarak celah granulasi, total jarak lateral-medial (lebar) jaringan granulasi, serta perhitungan besar volume jaringan granulasi. Ditemukan percepatan re-epitelisasi yang bermakna secara statistik (P < 0,05) pada olesan dengan aloe vera (P = 0,003) dan madu (P = 0,004). Pada pembentukan jaringan granulasi kecuali tinggi jaringan granulasi yang tidak berbeda bermakna (P = 0,054) semuanya menunjukkan hasil yang berbeda bermakna secara statistik. Percepatan pembentukan jaringan granulasi yang ditemukan pada olesan aloe vera dan madu berupa proses pembentukan jaringan granulasi dengan arah lateral-medial menuju pusat luka. Simpulan: Re-epitelisasi dan pembentukan jaringan granulasi luka eksisi full-thickness pada telinga kelinci secara bermakna meningkat oleh pemberian aloe vera dan madu secara topikal; juga pemberian aloe vera sama efektifnya dengan madu dalam re-epitelisasi dan pembentukan jaringan granulasi. Kata kunci: aloe vera, madu, re-epitelisasi, pembentukan jaringan granulasi.